A new species of Bolitoglossa (Caudata, Plethodontidae) from the continental divide of western Panama - Hertz, Andreas; Lotzkat, Sebastian; Köhler, Gunther (Zootaxa, 2013)
We describe the new salamander species Bolitoglossa jugivagans from the Atlantic slopes of the Fortuna depression in western Panama on the basis of morphological and molecular data. Based on mtDNA data, the new species seems to be closely related to B. aureogularis and B. robinsoni, with which it forms a subclade within the subgenus Eladinea.